KEADILAN SUBSTANTIF DALAM PENANGANAN PELANGGARAN TSM PEMILIHAN (Jurnal Huma Betang Demokrasi, 2021)
One of the instruments for upholding election justice is through the enforcement of election law by designing a legal framework that regulates effective mechanisms and settlements. However, election law enforcement does not reflect justice frequently due to law enforcement that is too positivistic oriented so that the justice is realized only formal justice based on law (procedural/conventional justice). Based on this fact, it is necessary to know and formulate the construction of progressive law enforcement based on the value of substantive justice, especially in handling election administrative violation in a structured, systematic and massive.